METAPHORS IN COFFEE ADVERTISING SLOGANS - Arifatin, Fais Wahidatul (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2019)
Conceptual metaphors are noticeable in everyday life, not just in language but in thought and action. They can be found in many life aspects such as advertisements. Through advertising slogans of products, especially coffee, metaphors are used. This paper aims are to: identify and analyze both the conceptual metaphors and the creative metaphorical linguistic expressions used in coffee advertising slogans and the possible reasons why a certain source domain is chosen for coffee target domain. The findings of this paper are that conceptual metaphors are used extensively in coffee advertising slogans to arouse customers? interest. Good and creative coffee advertising slogans depend on well-chosen conceptual metaphors. This expands some new conceptual metaphors in our everyday life.Since advertising slogans contain brief and short sentences, even not in a full sentence, there could be more than one possible interpretation for each slogan. Different people may have different interpretation. No matter the understanding achieved, the advertising slogans main focus is to deliver a positive message and to promote the products.